2022
DOI: 10.52225/narra.v2i2.80
|View full text |Cite
|
Sign up to set email alerts
|

Challenges on tuberculosis care in health care facilities during COVID-19 pandemic: Indonesian perspective

Abstract: Indonesia is among the top three countries globally with the highest tuberculosis  burden. During the past decades, Indonesian health authorities have struggled to improve tuberculosis care quality in health care facilities by optimizing the regulation and strengthening the private sector contributions. The coronavirus disease 2019 (COVID-19) pandemic has hardly affected the Indonesian health care system, including the National Tuberculosis Control Program. While the end of the COVID-19 pandemic in Indonesia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, the current literature has primarily focused on TB health service disruptions. For example, in the case of both India [ 60 ] and Indonesia [ 61 ], studies have shown that a potential contributor to diminished diagnoses is that health centers temporarily stopped or reduced TB health services in order to focus more on COVID-19 services. For China, strict internal movement restrictions and reduced access to TB diagnostic equipment were cited as drivers for the drops in TB diagnoses among patients [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the current literature has primarily focused on TB health service disruptions. For example, in the case of both India [ 60 ] and Indonesia [ 61 ], studies have shown that a potential contributor to diminished diagnoses is that health centers temporarily stopped or reduced TB health services in order to focus more on COVID-19 services. For China, strict internal movement restrictions and reduced access to TB diagnostic equipment were cited as drivers for the drops in TB diagnoses among patients [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, the pandemic led to the closure of healthcare facilities (HCFs), diversion of medical personnel toward COVID-19 prevention and treatment, reduced access to TB laboratory services and delays in follow-up visits for individuals with TB. [7][8][9][10] Additionally, several studies of public HCFs in Indonesia have shown that investigation of presumptive TB cases decreased during the pandemic, along with TB case notification rates and TB treatment coverage. 11 12 In contrast, a study of private HCFs reported no major changes in the quality of tuberculosis care due to the COVID-19 pandemic.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Handling TB in Indonesia during the COVID-19 pandemic has become increasingly complex and challenging, as noted in recent reports (26). The fear of visiting health services for TB treatment, combined with the reduction of active or passive TB case-finding activities due to a shift in focus toward COVID-19 contract tracing, has led to a decline in reported TB cases (24,25).…”
Section: Challengesmentioning
confidence: 99%